2010
DOI: 10.4314/njsr.v8i1.54818
|View full text |Cite
|
Sign up to set email alerts
|

Arterial trauma of the extremities. An Ivorian surgical experience(Côte d’Ivoire)

Abstract: Objective: The goal of this retrospective study is to present our epidemiological , clinical and surgical experience of the arterial injuries of extremities for 23 years (1977 to 2000). Materials and Methods: 35 patients were operated on over the study period. Their case files have been reviewed and forms the subject of this study Results: 30 were men and 5 women with an age range of 14 months -63 years and a median age of 25.4 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…EMF extended most frequently to all the endocardium, sticking the chordaes, the papillary muscles and the valvular tissues; what justifies the predominance of valvular replacement rather than valve repair in our study. Hospital mortality was high in the literature: 20% for Moraes (60)(61)(62), 16% for Metras (63); in our study on bilateral EMF in children we reported an early mortality after surgery at 29.4% (64). Fibrosis is not recurring as evocated by Tharakan (59); it indicates the end of a pathological process and the proof was given during an autopsy carried out in Abidjan with a patient 4 years after a right EMF surgery (65).…”
Section: Emfsupporting
confidence: 44%
“…EMF extended most frequently to all the endocardium, sticking the chordaes, the papillary muscles and the valvular tissues; what justifies the predominance of valvular replacement rather than valve repair in our study. Hospital mortality was high in the literature: 20% for Moraes (60)(61)(62), 16% for Metras (63); in our study on bilateral EMF in children we reported an early mortality after surgery at 29.4% (64). Fibrosis is not recurring as evocated by Tharakan (59); it indicates the end of a pathological process and the proof was given during an autopsy carried out in Abidjan with a patient 4 years after a right EMF surgery (65).…”
Section: Emfsupporting
confidence: 44%